Musical protest and revolutionary media: capital transformation among artists, activists, and journalists during the 14 January Revolution - Mannone, Nathanael (AUC Knowledge Fountain, 2012)
This thesis examines the transformations of cultural, symbolic and material capital (and power) both within and among the fields of music, activist, and journalism during the recent uprising in Tunisia. Analyzing a selection of Tunisian music juxtaposed to several ubiquitous conjectures in the news media, I also challenge the role music is purported to have played in these revolutions. In recent months, many in the international press and music industry have credited hip-hop artists in Tunisia as being a driving force in the 14 January Revolution. Many cite substantially increased levels of outspokenness among the artist community against the regime and therefore locate a significant rupture with past traditions. However, by analyzing the past decade one can find many examples of artists, bloggers, workers, and activists speaking out against the regime, thus the contention that an unprecedented level of activism arouse among the artist community requires further analysis. In addition, the function that the international news media played in the revolution via the elevation of certain artists (and thus consecration of their musical-activist capital) is often ignored or unacknowledged. Evidence suggests however, that the artists in question seemed implicitly aware of this dynamic and often used it to their advantage. It is clear that music, as a cultural production both influences and mirrors widespread public opinion(s). The interplay between political music and public sentiment is instructive when examined through transformations of capital; particularly because much intangible capital can be converted to other forms of capital when the artist is lauded by international observers. Additionally, by locating the regime of Ben Ali and dissident artists at opposing loci, and placing a linear hierarchy between them, the (often foreign) analysts ignore the breadth of power dynamics both within the macro-hierarchy that they propose, within the media, as well as within the music industry itself.